P-196 Increases in Use of Robotic Surgical Platforms for the Treatment of IBD: A Single Institution's Experience. (February 2017) - Stringfield, Sarah; Harnsberger, Cristina; Parry, Lisa; Ramamoorthy, Sonia; Eisenstein, Samuel
Abstract : Background: Patients with Inflammatory Bowel Disease (IBD) are difficult to manage operatively and historically have a high rate of post-operative complications. Patients with IBD also frequently require multiple operations throughout the course of their disease. Minimally invasive surgery techniques have shown advantages over open surgery in terms of recovery time, better cosmetic outcomes, and shorter hospitalizations. Minimally invasive surgery has become more widely used over the past several years as the technology, specifically robotic surgery, has been more widely adopted. The aim of this paper is to review use and outcomes of minimally invasive surgery in IBD patients at an academic institution. Methods: Retrospective review of patients with IBD who underwent a minimally invasive abdominal colorectal surgery at our institution between June 2014 and July 2016. Preoperative, perioperative, and postoperative data was collected. Preoperative data was collected within 14 days of surgery. Complications were defined as Clavien-Dindo grade II-IV occurring within 30 days of surgery. Categorical variables were analyzed using Fisher's exact test or Chi-square test and continuous variables were analyzed using 2-sided t test for independent means. Results: We identified 184 abdominal colorectal operations performed on 124 patients with IBD. Open operations accounted for 43% (79/184), laparoscopic were 36% (66/184), and robotic operations were 21% (39/184) of the total operations. The most common operations performed included subtotal colectomy with end ileostomy or completion proctectomy with ileum to anal anastomosis and diverting loop ileostomy (72/184, 39%). These cases were predominantly performed in a minimally invasive technique. The next most common minimally invasive operation performed was ileocolic resection (1 robotic, 12 lap). Subtotal colectomy and completion proctectomy accounted for 85% (33/39) of robotic operations and 47% (31/66) of laparoscopic cases. Only 8 were performed open. Over time, the use of robotics for these operations has increased. In 2014, 27% were performed robotically and 73% laparoscopically, compared to 63% robotic and 38% laparoscopic in 2016. Compared to laparoscopic cases, robotic subtotal colectomy or completion proctectomy had similar intraoperative blood loss (114 mL robotic versus 102 mL lap, P = 0.73), rate of intraoperative transfusions (6% versus 6%, P = 1.0) or postoperative transfusion (12% versus 19%, P = 0.5), conversion to open (3% versus 3%, P = 1.0), and post-operative length of stay (5.9 versus 5.6 d, P = 0.72). Robotic cases had significantly longer operative time (341 versus 275 min, P = 0.0023). Overall rate of postoperative complications did not vary between operative techniques (33% versus 39% of cases, P = 0.8) and all complications were Clavien-Dindo grade II or III. Thirty-day readmission rate was also similar between modalities (9% versus 3%, P = 0.6). Conclusions: The majority of subtotal colectomies and completion proctectomies performed at our institution over the past 2 years were performed in a minimally invasive technique. The proportion of cases performed robotically has increased over time and is now the preferred method. There are no significant differences in outcomes when comparing robotic to laparoscopic operations, except for a longer operative time for robotic surgery.